John Chrysostom’s Discourse on Property Ownership: An Analysis from the Perspective of Roman Law - Yingxue, Chen (Vox Patrum, 2022)
Unlike the dominant but simplified view of previous scholarship that Chrysostom stands in opposition to Roman property law, his attitude towards Roman law concerning property ownership is quite complicated. Insisting on the belief that things are created for common use and God is the ultimate owner of the world, Chrysostom denies various modes of property acquisition approved by Roman law (inheritance, thesauri inventio, and specificatio ) to be righteous, but when clarifying the limited and inferior human right over things in comparison with that of God, he never hesitates to use the Roman legal terms χρῆσις and δεσποτεία. Moreover, based on the conviction that the worldly economic order derives from divine providence, he confines his enumeration of the things shared in common mainly to the Res communes and Res publicae or Res universitatis under Roman law and persuades his audience to help those in need with the wealth temporarily under their stewardship. As a rhetorical strategy, Chrysostom’s use and manipulation of Roman legal language and thought aimed to promote almsgiving